Implementation of ISBT 128 Compatible Medical Record System to Facilitate Traceability of Stem Cell Products - Boga, Can; Maytalman, Erkan; Gereklioglu, Cigdem; Asma, Suheyl; Kandemir, Fatih; Aytan, Pelin; Korur, Aslı; Yeral, Mahmut; Kozanoglu, Ilknur; Ozdogu, Hakan (Turkish journal of haematology, 2017)
Cellular therapy production codes beginning with 'S' were checked against the International Council for Commonality in Blood Banking Automation registry and unique identifiers for patient, donor, and stem cell products were produced. Keywords: Hematopoietic stem and progenitor cells, Stem cell mobilization, Apheresis, ISBT 128, JACIE, Labeling, Traceability Anahtar Sözcükler: Hematopoietik stem ve progenitor hücreler, Stem hücre mobilizasyonu, Aferez, ISBT 128, JACIE, Etiketleme, Takip edilebilirlik Conflict of Interest: The authors of this paper have no conflicts of interest, including specific financial interests, relationships, and/or affiliations relevant to the subject matter or materials included. American Association of Tissue Banks, American Red Cross, American Society for Blood and Marrow Transplantation, American Society for Apheresis, America's Blood Centers, Foundation for the Accreditation of Cellular Therapy, ICCBBA Inc., International Society for Cellular Therapy, National Marrow Donor Program.